2017
DOI: 10.1111/1365-2656.12611
|View full text |Cite
|
Sign up to set email alerts
|

Seal mothers expend more on offspring under favourable conditions and less when resources are limited

Abstract: In mammals, maternal expenditure on offspring is a complex mix of several factors including the species' mating system, offspring sex and the condition and age of the mother. While theory suggests that in polygynous species mothers should wean larger male offspring than females when resources and maternal conditions allow, the evidence for this remains equivocal. Southern elephant seals are highly dimorphic, polygynous capital breeders existing in an environment with highly variable resources and should theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
64
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 68 publications
4
64
1
Order By: Relevance
“…Even though this is a small change, the overall rate of decline for the Macquarie Island population of breeding females is less than 1% per annum. A very small but long-term change in first year survival (through a small change in weaning size) is therefore sufficient to generate this insidious rate of decline [38]. This also accords with a previous study at Marion Island which found that mean weaning mass was smaller than the long-term average during a period of population decline, with a sudden reversal in the growth rate of the population preceded by an increase in mean weaning mass [11].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Even though this is a small change, the overall rate of decline for the Macquarie Island population of breeding females is less than 1% per annum. A very small but long-term change in first year survival (through a small change in weaning size) is therefore sufficient to generate this insidious rate of decline [38]. This also accords with a previous study at Marion Island which found that mean weaning mass was smaller than the long-term average during a period of population decline, with a sudden reversal in the growth rate of the population preceded by an increase in mean weaning mass [11].…”
Section: Discussionsupporting
confidence: 86%
“…Elephant seal mothers tend to wean relatively larger male pups compared to females when foraging conditions in the winter are good [13, 3638]. Therefore, the larger weaners at Heard Island during the 1950s suggests that the overall condition of mothers from Heard Island during this period was better than those from Macquarie Island.…”
Section: Discussionmentioning
confidence: 99%
“…There is a cost to mothers when conditions are poor because they produce and wean smaller pups with lower survival prospects (McMahon, Harcourt, Burton, Daniel, & Hindell, 2017;McMahon, New, Fairley, Hindell, & Burton, 2015), negatively influencing population growth New, Clark, & Costa, 2014;Schwarz, Hindell, McMahon, & Costa, 2012). Firstly, there was limited spatial context available, and so clear regional attribution for the observed differences could not be made.…”
Section: Our Knowledge Of the Basic Biology And Distribution Of Southernmentioning
confidence: 99%
“…It has been seen in southern elephant seals at Macquarie Island that during favorable conditions, mothers will invest more energy in their offspring than when resources are limited (McMahon et al . ). If prey availability in region A and B on the shelf is limited, the findings in this study could provide evidence for intraspecific competition.…”
Section: Discussionmentioning
confidence: 97%